2017
DOI: 10.1111/maq.12391
|View full text |Cite
|
Sign up to set email alerts
|

Buffering the Uneven Impact of the Affordable Care Act: Immigrant‐serving Safety‐net Providers in New Mexico

Abstract: We conducted a study in early 2014 to document how the initial implementation of the Affordable Care Act (ACA) affected health care provision to different categories of immigrants from the perspective of health care providers in New Mexico. Though ACA navigators led enrollment, a range of providers nevertheless became involved by necessity, expressing concern about how immigrants were faring in the newly configured health care environment and taking on advocacy roles. Providers described interpreting shifting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Studies have found that in recent decades the cost of work‐related injuries and illnesses has shifted away from workers' compensation to workers and their families, private health insurance, and the government 15,49–51 . Clinicians' observations regarding the delivery of care to injured Latina/o workers suggests some community clinics are also taking on the financial burden of providing care to injured workers and buffering against the gaps in care for Latina/o immigrants stemming from the current structure of the workers' compensation system and lack of a universal healthcare policy 52,53 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that in recent decades the cost of work‐related injuries and illnesses has shifted away from workers' compensation to workers and their families, private health insurance, and the government 15,49–51 . Clinicians' observations regarding the delivery of care to injured Latina/o workers suggests some community clinics are also taking on the financial burden of providing care to injured workers and buffering against the gaps in care for Latina/o immigrants stemming from the current structure of the workers' compensation system and lack of a universal healthcare policy 52,53 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated how community health workers (CHWs) in particular deploy CCW to improve community health and well-being through advocacy and research [25,26] However, these studies do not elaborate how health care workers deploy their CCW specifically in health care settings. A separate literature on health care brokerage examines how immigrants and coethnics serve as intermediaries in facilitating immigrants' interface with the health care system [27][28][29][30][31]. Brokers are prized for their ability to flex to meet community needs and performing tasks that often extend beyond their envisioned or funded positions [32,33].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Medical anthropologists have produced important insights into the geography of care in the rural United States. Ethnographers have repeatedly found that safety net institutions and the health care providers who work at them fill gaps created by the privatization of health care services (Boehm 2005;Horton et al 2001) as well as the categorical exclusion of many immigrants from coverage (Getrich et al 2017). Thurka Sangaramoorthy (2018) argues that safety net care is improvisational and incomplete, forcing dedicated care providers to employ multiple informal strategies to deliver care such as bartering, rationing, hoarding, willful noncompliance, and goodwill.…”
Section: Uncare As Red State Policy: Dismantling the Safety Netmentioning
confidence: 99%